Quantitative assessment of the inflammatory reaction in the anterior chamber of the eye according to optical coherent tomograrhy data in standard cases of routine cataract surgery and in patients with concomitant ophthalmological and systemic pathology - A. N. Kulikov; E. V. Danilenko; D. V. Tulin; A. A. Dzilihov; N. V. Nevin; A. R. Kuznetsov (Российский офтальмологический журнал)
Purpose: to determine the risk factors of the inflammatory reaction in the anterior chamber aqueous humor in routine cataract surgery of patients with concomitant ophthalmological and systemic pathology based on a quantitative assessment of the eye anterior segment optical coherent tomography (OCT) data.Material and methods. The study enrolled 60 patients aged 38 to 85 years, 45 % of them were men. Before planned phacoemulsification, a standard ophthalmological examination, the eyelids status assessment, parameters of the lacrimal meniscus, calculation of cell in the anterior chamber using OCT were performed, also general clinical data were analyzed. 2 groups were analyzed: group 1 — risk group — 30 patients with symptoms of inflammatory reaction according to a blood test, paraocular foci of chronic infection and diabetes mellitus, as well as those who had chronic blepharitis, group 2 control — 30 patients without these signs. Biomicroscopy and anterior segment OCT were performed before and 4 hours after the surgery, as well as on days 1, 7, and 14.Results. Group 1 patients had cytosis of 2.5 cells (0-20) in the anterior chamber humor at the preoperative stage. Cells were detected in 57.58 % of cases (p = 0.000), but in no case in group 2. In the first hours after surgery, the same frequency of humor opalescence fibrinoid reaction and ophthalmohypertension was observed in the groups, but the frequency of corneal tunnel edema in group 1 was significantly higher (p = 0.048). In the first hours after the intervention, the cell suspension in the aqueous humor was more intense in patients of the risk group; in all cases the number of cells progressively decreased and leveled out between the groups. Correlation analysis showed the relationship between the severity of cell suspension and opalescence of the anterior chamber humor with the presence of cytosis at the preoperative stage (R = 0.88, p = 0.002), the type of IOL chosen (R = 0.74, p = 0.021) and the presence of diabetes mellitus in history (R = 0.82, p = 0.007).Conclusions. Usage of precise imaging techniques to assess anterior chamber humor cytosis is a convenient, objective, and reliable method. The presence of cell suspension in the anterior chamber aqueous before surgery, especially in elderly patients with diabetes mellitus, is a prognostic factor for a more expressed inflammatory reaction of the anterior segment in uncomplicated phacoemulsification.